Death and gender in the early modern period - Fernández, Enrique 1961-; Abreu-Ferreira, Darlene (Brill, 2024)
In late medieval and early modern Europe, death could reinforce, question or efface the category of gender, as evidenced by the preparation for death, executions, burial practices and the cult of the dead.
Keywords: Geschichte 1450-1800; Geschlecht; Sexualität; Bestattung; Sterben; Grabmal; Gender; Jenseits; Tod; Sexualverhalten; Europa; Aufsatzsammlung